2006
DOI: 10.1002/ijc.22022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prostate cancer: A national case‐control study

Abstract: Statutory notification of cancer in New Zealand provided an opportunity to investigate risk factors for prostate cancer in a large national population-based case-control study. We analyzed data obtained from telephone interviews with 923 cases and 1,224 controls. For inclusion in the study, all subjects had to have been married at some time. We found an increased risk of prostate cancer among those with a history of prostate cancer in first degree relatives (RR 2.6; 95% CI, 1.9-3.7) and an increased risk of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Associations between height and clinically relevant prostate cancer have been examined (16,21,24,(29)(30)(31)(33)(34)(35), with stronger associations observed for more advanced versus localized disease in several studies (24,(29)(30)(31), which is in accord with the present findings. For example, a particularly strong association between tallness and aggressive prostate cancer was noted in the Auckland Prostate Study for men taller than 179 cm who also had a positive family history of prostate cancer, although stratum-specific sample sizes were small (HR, 7.41; 95% CI, 1.68-32.67; P trend = 0.02; ref.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Associations between height and clinically relevant prostate cancer have been examined (16,21,24,(29)(30)(31)(33)(34)(35), with stronger associations observed for more advanced versus localized disease in several studies (24,(29)(30)(31), which is in accord with the present findings. For example, a particularly strong association between tallness and aggressive prostate cancer was noted in the Auckland Prostate Study for men taller than 179 cm who also had a positive family history of prostate cancer, although stratum-specific sample sizes were small (HR, 7.41; 95% CI, 1.68-32.67; P trend = 0.02; ref.…”
Section: Discussionsupporting
confidence: 86%
“…Case-control studies have reported predominantly weak or no associations (4,10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), whereas several cohort studies found statistically significant elevations in risk (27)(28)(29)(30)(31)(32)(33). Eight studies have specifically evaluated height as a risk factor for clinically advanced cancer (16,21,24,(29)(30)(31)(33)(34)(35), with three reporting >50% increases in risk of advanced disease for men taller than 173 cm (24,29,30). Because the associations between height and prostate cancer seemed to be relatively modest in the aforementioned studies, large numbers of cases are required to detect small yet meaningful associations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these cancers have diverse underlying carcinogenic pathways. Smoking is a strong risk factor in bladder, lung, and head and neck cancer whereas it does not appear to be a significant prostate cancer risk factor, either in the present study or in many others (US Department of Health and Human Services, 2004; Cox et al. , 2006; Darlington et al.…”
Section: Discussioncontrasting
confidence: 54%
“…More than 30 prospective and 27 case -control studies have examined height and overall prostate cancer risk (Macinnis and English, 2006;Zuccolo et al, 2008), but findings are mixed; some studies showed a positive association (Le Marchand et al, 1994;Andersson et al, 1997;Giovannucci et al, 1997;Hebert et al, 1997;Rodriguez et al, 2001;Engeland et al, 2003;Cox et al, 2006;Sequoia et al, 2006;Zuccolo et al, 2008), whereas others found no relation (Severson et al, 1988;Cerhan et al, 1997;Veierod et al, 1997;Nilsen and Vatten, 1999;Clarke and Whittemore, 2000;Pischon et al, 2008). Stronger associations were observed for more advanced or fatal prostate cancer among 7 (Andersson et al, 1997;Giovannucci et al, 1997Giovannucci et al, , 2004Rodriguez et al, 2001;Cox et al, 2006;Sequoia et al, 2006;Zuccolo et al, 2008) of the 14 (Le Marchand et al, 1994;Andersson et al, 1997;Giovannucci et al, 1997Giovannucci et al, , 2004Nilsen and Vatten, 1999;Habel et al, 2000;Hsing et al, 2000;Norrish et al, 2000;Rodriguez et al, 2001;Macinnis et al, 2003;Cox et al, 2006;Sequoia et al, 2006;Pischon et al, 2008;Zuccolo et al, 2008) studies ...…”
Section: Discussionmentioning
confidence: 99%